A Meta-Analysis of GBA-Related Clinical Symptoms in Parkinson’s Disease - Yuan Zhang; Li Shu; Xun Zhou; Hongxu Pan; Qian Xu; Jifeng Guo; Beisha Tang; Qiying Sun (Parkinson's Disease)
Background. GBA gene had been proved to be a crucial gene to the risk of PD. Numerous studies had discussed about the unique clinical characteristics of PD patients with GBA carriers (GBA + PD). However, there was lack of updated comprehensive analysis on the topic. In order to clarify the association between GBA variants and the clinical phenotypes of PD, we conducted this comprehensive meta-analysis. Method. Medline, Embase, and Cochrane were used to perform the searching. Strict selection criteria were followed in screening for new published articles or data. Revman 5.3 software was applied to perform the total statistical analysis, and funnel plots in the software were used to assess the publication biases. Results. A total of 26 articles including 931 GBA + PD and 14861 GBA noncarriers of PD (GBA − PD) were involved in the final meta-analysis, and 14 of them were either newly added publications or related data newly analyzed compared with the version published in 2015. Then, a series of symptoms containing depression, orthostatic hypotension, motor fluctuation, wearing-off, and freezing were newly analyzed due to more articles eligible. Besides, clinical features like family history, AAO, UPDRS-III, H-Y, and dementia previously analyzed were updated with new data added. Significant statistical differences were found in wearing-off, family history, AAO, UPDRS-III, and dementia (OR: 1.14, 1.65; MD: −3.61, 2.17; OR: 2.44; p: 0.03, <0.00001, <0.00001, 0.003, and <0.00001). Depression was slightly associated with GBA + PD (OR: 1.47; p: 0.04). Clinical symptoms such as H-Y, orthostatic hypotension, motor fluctuation, and freezing did not feature GBA + PD. Conclusion. Our results demonstrated that there were unique clinical features in GBA + PD which can help the management of the whole duration of PD patients.